PENGARUH HARGA, KUALITAS PELAYANAN DAN WORD OF MOUTH TERHADAP MINAT BELI ULANG (REPURCHASE INTENTENTION): Studi Kasus di Coffee Shop Kopi Dari Hati D’Kebon Selo Boyolali - Oktavianti, Arum; Lisdiana, Nuning; Rahayu, Listyowati Puji (EKOBIS, 2022)
The purpose of this study was to determine the effect of price, service quality and word of mouth on repurchase interest. The population in this study were consumers of coffee from Hati D'Kebon Selo Boyolali. The technique of collecting data is by distributing questionnaires with a sample of 100 respondents using the Accidental Sampling method. The research method is quantitative and descriptive analysis of case studies. Testing of data instruments was carried out with validity and reliability tests, for data analysis using normality test, autocorrelation test, t test and f test and determination test (R2) was used to test the hypothesis. Validity test, reliability test and classical assumption test that have been fulfilled are then processed to produce the regression equation: Y = 1.885 + 0.149 X1 + 0.205 X2 + 0.683 X3. Through partial t test hypothesis testing, the price variable does not affect the repurchase intention variable, while the service quality variable and word of mouth affect the repurchase interest variable. It is stated that the results of the determination test (R2) that Rsquare is 0.656, this indicates that the price, service quality, and word of mouth variables together can explain the variable of repurchase interest of 66.7%, the remaining 33.3% can be explained by other variables, in addition to variables. investigated in this study